A photochromic–acidochromic HCl fluorescent probe. An unexpected chloride-directed recognition12. Issue 13 (9th May 2016) - Jiménez-Sánchez, Arturo; Santillan, Rosa
Abstract : A fluorescent-chromogenic Schiff base probe displays multiresponsive properties and specific interactions with HCl giving an acidofluorochromic response to light (photochromism) and the nature of the solvent (solvatochromism). Abstract : Non-classical protomerism of Schiff bases offers several advantages; for example, specific interactions in the –CN– linkage can be controlled and differentiated because the interactions are not governed by keto – enol tautomerism. Herein, the pH sensing properties of a new protomeric Schiff base probe (S1 ) are reported. In particular, among several acids, the probe displays significant optical responses upon interaction with hydrochloric acid (HCl). X-ray structural analysis confirmed the existence of an intermolecular interaction with HCl through a –CN⋯H–Cl⋯O– linkage. Moreover, an optical response via a second channel is manifested as photochromic fluorescence behavior. The properties ofS1 were investigated by UV-vis and fluorescence spectroscopy in a solution and the solid state. Its strong acidofluorochromic behavior was analyzed and its p K a and values were determined, which revealed a photobasic character. Positive solvatochromism that resulted from specific interactions taking place inS1 was studied using four different solvent scales, namely, Lippert–Mataga, Kamlet–Taft, Catalán and the recently proposed scale of Laurence et al., which yielded consistent results. Finally, theoretical calculations were conducted to analyze the mechanism of the probe in terms of natural transition orbitals (NTOs) and the spatial extent of charge transfer excitations.